All the songs the story behind every Beatles release - Guesdon, Jean-Michel; Margotin, Philippe (Black Dog & Leventhal, 2013)
Musical historians Phillippe Margotin and Jean-Michel Guesdon delve deep into the history and musical origins of every Beatles album, recounting the circumstances that led to the composition of each song, the recording process, and the instruments used... This intimate and revealing look at the music of The Beatles draws on decades of research. For example, readers learn that one of John Lennon's favorite guitars was a 1958 Rickenbacker 325 Capri, which he bought for 100 pounds in 1960 in Hamburg. He had it painted black and used it on the Ed Sullivan Show and in the Hollywood Bowl concerts. It now belongs to his son Sean... Readers will also get an inside look at each song's recording. Love Me Do was recorded in Abbey Road Studios in September 1962. The song took 18 takes to get right, though it was one of the first songs John and Paul had written together. John was originally supposed to sing lead vocals, but when George Martin suggested adding a harmonica, Paul took over as lead... Hundreds of photographs range from rare black-and-white publicity stills to images of Beatles instruments to intimate shots of the musicians in the studios. Special sections called 'For Beatles Addicts,' give even more detailed information for the true fan..
Franz. Ausg. u.d.T.: Les Beatles, la totale
Bibliography: page 671
Keywords: Beatles; The Beatles -- Musikgruppe; Geschichte; Rock music / Great Britain / 1961-1970 / History and criticism; Rock music / Writing and publishing / Great Britain; Song; Großbritannien; Verzeichnis